Strategic Cross-Trading in the U.S. Stock Market - Pasquariello, Paolo; Vega, Clara (Review of Finance, 2015)
Abstract We model and test for the role of heterogeneously informed, strategic multi-asset speculation for cross-price impact—the impact of trades in one asset on the prices of other (even unrelated) assets—in the U.S. stock market. Our investigation of the trading activity in New York Stock Exchange (NYSE) and National Association of Securities Dealers Automated Quotation System (NASDAQ) stocks between 1993 and 2004 reveals that, consistent with our model, (1) daily order imbalance in one industry or random stock has a significant, persistent, and robust impact on daily returns of other (even unrelated) industries or random stocks; (2) cross-price impact is often negative; and (3) both direct (i.e., an asset’s own) and absolute (i.e., unsigned) cross-price impact are smaller when speculators are more numerous, greater when market-wide dispersion of beliefs is higher, and greater among stocks dealt by the same specialist.